2010
DOI: 10.1016/j.pgeola.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeology of Pleistocene open-air sites in the Vila Nova da Barquinha-Santa Cita area (Lower Tejo River basin, central Portugal)

Abstract: This paper aims to provide insight into human occupation and landscape change during the Pleistocene in a central area of the Lower Tejo basin (Portugal). Detailed geomorphological mapping, coupled with lithostratigraphy, sedimentology and luminescence dating, supports the identification of a complete terrace staircase sequence. It consists of six gravely terraces located below the culminant (Pliocene) basin unit. A chronological framework for the sedimentary sequences and associated human industries is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 24 publications
0
40
0
9
Order By: Relevance
“…5C, D). These finds are from sandy and sometimes organic beds within a complex sequence forming Terrace 4 of the Tagus in its lower Portuguese reach, regarded as Late Pleistocene by Mozzi et al but now shown to be significantly older by subsequent research, including optically stimulated luminescence dating (Martins et al 2010). This is, of course, an isolated point of comparison and is floated here as an indication of the type of evaluation of artefact assemblages that might be fruitful in future.…”
Section: Wider Comparisonsmentioning
confidence: 74%
“…5C, D). These finds are from sandy and sometimes organic beds within a complex sequence forming Terrace 4 of the Tagus in its lower Portuguese reach, regarded as Late Pleistocene by Mozzi et al but now shown to be significantly older by subsequent research, including optically stimulated luminescence dating (Martins et al 2010). This is, of course, an isolated point of comparison and is floated here as an indication of the type of evaluation of artefact assemblages that might be fruitful in future.…”
Section: Wider Comparisonsmentioning
confidence: 74%
“…In reach III, the Tejo is routed EeW, crossing three structural depressions with a Tertiary cover (Martins et al, 2009). In reach IV, the Tejo changes to a NNEeSSW trend, with valley sides displaying different degrees of terrace staircase development (Martins et al, 2010a(Martins et al, , 2010b (Figs. 1 and 2).…”
Section: Pp Cunha Et Al / Quaternary Science Reviews XXX (2016) 1ementioning
confidence: 99%
“…The high amplitude sea-level changes that characterized the Middle and Late Pleistocene controlled the episodic down-cutting phases of the river during sea-level lowstands; these alternated with flooding and agradation phases in the incised valley during highstands . Such climate related eustatic oscillations are superimposed onto a long-term uplift pattern, both phenomena having controlled the river terrace staircase development (Cunha et al, 2005(Cunha et al, , 2008Martins et al, 2010aMartins et al, , 2010b.…”
Section: Pp Cunha Et Al / Quaternary Science Reviews XXX (2016) 1ementioning
confidence: 99%
“…En el curso bajo del río Tajo (Portugal), las dataciones OSL disponibles (Cunha et al, 2008(Cunha et al, , 2012Martins et al, 2009Martins et al, , 2010 indican que las terrazas de c. +30−48 m, con edades de c. 260-340 ka, poseen industrias achelenses (Monte do Famaco), mientras que la terraza inmediatamente inferior (+16−28 m) posee industrias claramente musterienses con fechas comprendidas entre 135 ka (base) y 73 ka (techo), dentro del tránsito Pleistoceno Medio-Superior (MIS 6 -MIS 5). Estas cronologías más recientes son también características de las unidades superiores de las terrazas complejas a +18-20 m en los valles del Jarama y Manzanares (Panera et al, 2011;Pérez-González et al, 2013;Silva et al, 2013).…”
Section: Interpretaciónunclassified